Bidens pilosa L.: Botani, Manfaat, dan Bioaktivitasnya - Marina Silalahi; Mercy Silalahi; Ratna Kristiani Nababan (Pro-Life, 2021)
Bidens pilosa belonging Asteraceae has been long used by humans as food and traditional medicine. This study aims to explain the relationship between utilization and bioactivity of B. pilosa. The method writing this article is a literature study of the benefits and bioactivity of B. pilosa which is published online on google scholar. The keywords used in the article search were B. pilosa, uses of B. pilosa and bioactivity of B. pilosa. The literature was synthesized so that it explains comprehensively the benefits and bioactivity of B. pilosa. Bidens pilosa by local communities used to treat malaria, diabetes mellitus, inflammation, hypertension, anti-inflammatory, cancer, immune modulation, and anti-bacterial. The bioactivity of B. pilosa such as anti-oxidant, anti-cancer, anti-microbial, anti-diabetic mellitus, immunomodulators, anti-hypertension, anti-malarial, hepatoprotective and analgesic. The bioactivity of B. pilosa as anti-cancer and anti-malaria is related to the phenyl-1,3,5-heptatriyne content. Antioxidant B. pilosa is related to the content of polyphenols and quercetin 3,3 -dimethyl ether 7-O-b-D-glycopyranoside. Bidens pilosa has the potential to be developed as a nutraceutical, which is a food ingredient that provides health effects.